2015
DOI: 10.1002/ghg.1541
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a thermally stable imine and benzimidazole functionalized nanoporous polymer (IBFNP) for CO2 capture application

Abstract: An imine and benzimidazole functionalized nanoporous polymer (IBFNP) has been synthesized by a single‐step condensation reaction between 3,3´‐diaminobenzidene and terephthaldehyde at 150 °C. The IBFNP‐1 has a moderately high BET specific surface area of 1040 m2/g with pore diameter centered at 1.4 nm and pore volume of 1.46 cm3/g. The IBFNP‐1 could reversibly capture 5.27 mmol/g (23.2 wt%) of CO2 at 273 K and 1 atm, which is among the best reported microporous organic polymers. The good selectivity of CO2 over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The CO 2 capture capacity of NENP-1 was estimated to be 22.9 wt % at 273 K and 1 bar (Figure 3b). The adsorption capacity is comparable to the recently reported high surface area polymeric frameworks such as NC-650-3 (30.8 wt %), 18 RN-500-3 (31.4 wt %), 19 NGC-650-4 (27.4 wt %), 21 WSC-450-2 (26.5 wt %), 22 bipy-CTF600 (24.5 wt %), 29 CHNM-1 (22.8 wt %), 34 PCTP-1 (21.6 wt %), 45 MCTP-1 (20.4 wt %), 57 PPF-1 (26.8 wt %), 58 BILP-4 (23.5 wt %), 59 IBFNP-1 (23.2 wt %), 60 TBILP-2 (22.8 wt %), 61 HAT-CTF-450/600 (27.7 wt %), 62 and higher than many other recent reports such as CTF-20-400 (15.3 wt %), 30 CTF-DCE (19.1 wt %), 31 HNM-1 (18.9 wt %), 32 PAF-3 (15 wt %), 63 azoCOP-2 (11.2 wt %), 64 and APOP-3 (19.9 wt %). 65 A comprehensive comparison of the CO 2 capture capacity of some of the recently reported porous organic frameworks is given in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 capture capacity of NENP-1 was estimated to be 22.9 wt % at 273 K and 1 bar (Figure 3b). The adsorption capacity is comparable to the recently reported high surface area polymeric frameworks such as NC-650-3 (30.8 wt %), 18 RN-500-3 (31.4 wt %), 19 NGC-650-4 (27.4 wt %), 21 WSC-450-2 (26.5 wt %), 22 bipy-CTF600 (24.5 wt %), 29 CHNM-1 (22.8 wt %), 34 PCTP-1 (21.6 wt %), 45 MCTP-1 (20.4 wt %), 57 PPF-1 (26.8 wt %), 58 BILP-4 (23.5 wt %), 59 IBFNP-1 (23.2 wt %), 60 TBILP-2 (22.8 wt %), 61 HAT-CTF-450/600 (27.7 wt %), 62 and higher than many other recent reports such as CTF-20-400 (15.3 wt %), 30 CTF-DCE (19.1 wt %), 31 HNM-1 (18.9 wt %), 32 PAF-3 (15 wt %), 63 azoCOP-2 (11.2 wt %), 64 and APOP-3 (19.9 wt %). 65 A comprehensive comparison of the CO 2 capture capacity of some of the recently reported porous organic frameworks is given in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 sorption isotherm measured at 273 K and 1 bar, given in Figure c, shows the CO 2 uptake of 22.8, 18.3, and 16.4 wt % for CHNM-1, CHNM-2, and CHNM-3, respectively. The CO 2 uptake of CHNM-1 is better than many reported high-surface-area solid sorbent such as PECONF-3, MPC-700, PAF-3, HNM-1, HCMP-1, and CZ@PON and comparable to many top-performing reported high-surface-area solid adsorbents such as PPF-1, ALP-1, BILP-4, BILP-6-NH 2 , and IBFNP-1 (for more details, see Supporting Information, Table S3). At 298 K, as expected, the CO 2 uptake decreases to 14.1, 10.5, and 8.9 wt % for CHNM-1, CHNM-2, and CHNM-3, respectively (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Among the well-investigated functional groups is benzimidazole which attracted a great deal of attention because of its chemical stability and optimal p K a that favors physisorptive interactions with CO 2 . , Aniline-like amine functionalities are also of interest because of the ideal p K a of aniline as opposed to alkyl amines where localized electron density on the nitrogen atoms results in chemisorption of CO 2 via carbamate formation. Chemisorption of CO 2 is not ideal because high temperatures are then required to regenerate the sorbent . It was shown recently that POPs containing multiple functional groups exhibit combined effects of each functional group that improve selective binding of CO 2 . For example, we have shown that the incorporation of triazine groups in benzimidazole linked polymers (BILPs) results in improved selective CO 2 capture capabilities . Because the amine functionality is known for improved CO 2 capture and separation by porous adsorbents, we hypothesized that placing amine groups adjacent to benzimidazole units in BILPs would increase CO 2 binding capabilities through multiple interactions and/or providing extra adsorption sites.…”
Section: Introductionmentioning
confidence: 99%